2021
DOI: 10.1039/d0sc07054h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and reactivity study of non-heme high-valent iron–hydroxo complexes

Abstract: A terminal FeIIIOH complex, [FeIII(L)(OH]2– (1), has been synthesized and structurally characterized (H4L = 1,2-bis(2-hydroxy-2-methylpropanamido)benzene). The oxidation reaction of 1 with one equiv. of tris(4-bromophenyl)ammoniumyl hexachloroantimonate (TBAH) or ceric ammonium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 62 publications
5
24
0
Order By: Relevance
“…In a recent study, Zhang and co-workers suggested the formation of ligand radical-coordinated cobalt­(III) complexes supported by a tetra-amido-macrocyclic ligand (TAML) during WO . We also recently characterized a ligand radical-coordinated iron­(III) complex, [Fe III (L 1 •+ )]­(OH)] − . Formation of such a ligand radical species likely stimulates the electrophilic nature of the copper­(III) center for further reaction with OH – .…”
Section: Resultsmentioning
confidence: 96%
“…In a recent study, Zhang and co-workers suggested the formation of ligand radical-coordinated cobalt­(III) complexes supported by a tetra-amido-macrocyclic ligand (TAML) during WO . We also recently characterized a ligand radical-coordinated iron­(III) complex, [Fe III (L 1 •+ )]­(OH)] − . Formation of such a ligand radical species likely stimulates the electrophilic nature of the copper­(III) center for further reaction with OH – .…”
Section: Resultsmentioning
confidence: 96%
“…Thesmall but significant CeÀObond difference between Ce À OEt of about 2.44 and Ce À OH 2 of 2.55 in average suggests that the coordinated alcohol is deprotonated. [13] Twoi dentical Ce III ions are bridged by carboxylic groups from four different ligands to constitute the unique dinuclear Ce 2 secondary building unit as af our-point connected node for undulating monolayer (Figures 1b and S2). Each deprotonated NAD + ligand acts as at wo-point connected node to connect two different Ce 2 units with two bidentate carboxylic groups and one monodentate oxygencoordinated carboxylic group,constructing athree-dimension porous framework with the shortest Ce•••N (NAD + )s eparation of approximately 5.59 (Figure 1b), which is beneficial for the synergy of two active sites between the NAD + fragments and Ce À OEt moieties inside the metal-organic framework skeleton structure.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of hydrogen atom transfer (HAT) reactions from organic substrates (SH) to metal-oxygen complexes, such as metal-oxo, metal-hydroxo, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] metal-(hydro)peroxo [40][41][42][43][44] and metal-superoxo, [45][46][47][48][49][50][51][52][53][54] have been investigated extensively, as summarized in Scheme 1. HAT proceeds via the transfer of both a proton and an electron which can be transferred simul-spectrum of "asynchronicity", in which the transition state for the HAT reaction can contain either more PT or more ET character (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of hydrogen atom transfer (HAT) reactions from organic substrates (SH) to metal–oxygen complexes, such as metal-oxo, 1–23 metal-hydroxo, 24–39 metal-(hydro)peroxo 40–44 and metal-superoxo, 45–54 have been investigated extensively, as summarized in Scheme 1. HAT proceeds via the transfer of both a proton and an electron which can be transferred simultaneously in a coupled fashion (concerted proton–electron transfer, CPET) or a stepwise fashion (proton transfer–electron transfer, PT/ET, or electron transfer–proton transfer, ET/PT) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%